1995
DOI: 10.1111/j.1423-0410.1995.tb02577.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous DNA Typing of Human Platelet Antigens 2, 3 and 4 by an Allele‐Specific PCR Method

Abstract: We developed an allele-specific polymerase chain reaction (ASPCR) method using originally designed primers to determine the genotype of the human platelet antigens (HPAs) 2, 3 and 4 in parallel. The results were compared with those obtained by PCR restriction fragment length polymorphism and the mixed passive hemagglutination test. Seventy-three individuals were tested and the ASPCR results were in good agreement with those determined by the other two methods. This method enables the genotyping of HPA-2, -3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This method is rapid, cost-effective, and suitable in large-scale platelet antigen genotyping, either for NAIT or in genetic population studies. 4,6,9,10,12,14,17 Furthermore, the distribution of HPA-1 to 6 phenotypes in Thai blood donors living in Bangkok is consistent with those found in Northeastern Thailand. 6,7 A previous study showed that the most common HPA antibodies in thrombocytopenic Thai patients were anti-HPA-5b, -HPA-2b, -HPA-3a, and unidentified antibodies.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This method is rapid, cost-effective, and suitable in large-scale platelet antigen genotyping, either for NAIT or in genetic population studies. 4,6,9,10,12,14,17 Furthermore, the distribution of HPA-1 to 6 phenotypes in Thai blood donors living in Bangkok is consistent with those found in Northeastern Thailand. 6,7 A previous study showed that the most common HPA antibodies in thrombocytopenic Thai patients were anti-HPA-5b, -HPA-2b, -HPA-3a, and unidentified antibodies.…”
Section: Discussionsupporting
confidence: 80%
“…The PCR-SSP technique has been shown to be a simpler and more reliable method for several HPA genotypes. [9][10][11][12][13][14] This study analyzed HPA-1 to 6 and Gov alleles, using PCR-SSP in Thai blood donors who had been HLA class I antigen typed to establish HPA-genotyped panels for identification of HPA antibodies in routine testing.…”
mentioning
confidence: 99%
“…HPA-1, -2, -3, -4, -5, and -6 genotypes were determined by PCR-SSP method as previously described. 1,2 In brief, the PCR reaction mixture (25 µL) contained 1X PCR buffer, 1.0 U of Taq DNA polymerase, 200 µmol/L of each dNTP, 1.8 mmol/L MgCl 2 , 0.5 µmol/L of each specific primer (Table 1), 0.2 µmol/L of internal control primer (to amplify human growth hormone gene), and 50 to 100 ng genomic DNA. PCR amplification was performed with initial denaturing at 95°C for 5 minutes followed by 30 cycles of 30 seconds at 95°C, 1 minute at 58°C (67°C for HPA-2, 63°C for HPA-3, 57°C for HPA-5 and HPA-6), and 45 seconds at 72°C plus a final extension at 72°C for 10 minutes.…”
Section: Hpa Genotypingmentioning
confidence: 99%
“…21 In our HPA-4 PCR-RFLP method, the presence of a mismatched T at the 3′ terminus of the modified primer is efficiently incorporated into the PCR product. 21 PCR-SSP, another DNA method used for platelet antigen typing, 14,22,23 also involves the use of modified PCR primers to distinguish HPA alleles. 24 In PCR-SSP, the PCR primer modifications are used to selectively amplify one HPA allele versus the other.…”
Section: Hpa-4 Genotyping Of Caucasian and North American Indian Populationsmentioning
confidence: 99%